2000
DOI: 10.1177/030802260006301207
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Activity Intervention in a Community Alcohol Service

Abstract: People recovering from alcohol-related or drug-related problems are often in poor physical condition and have an extremely sedentary lifestyle. This article describes a study in which an occupational therapist in a community alcohol service implemented a physical activity intervention. The aim of the intervention was for clients with substance misuse problems to increase independent physical activities, to engage more in community-based activities, to increase their awareness of the benefits of exercise and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…While there is a paucity of literature addressing the role of physical activity as a vehicle for helping bereaved children, there is a large body of research extolling the psychological health benefits of exercise. Studies have suggested that physical activity can enhance selfesteem (Fox, 2000), contribute to positive affect and mood (Biddle & Mutrie, 2001), help improve sleep (Arakawa et al, 2002;Morgan, 2003), reduce depression (Mutrie, 2000), help to manage the symptoms associated with schizophrenia (Carter-Morris & Faulkner, 2003), reduce stress (Read, Kahler, & Stephenson, 2001) and enhance body image (Ussher et al, 2000). Such evidence is particularly pertinent when we consider that bereaved children are more likely than other children to experience higher levels of depression, an increase in health problems and accidents, more anxiety and fear, lower self-esteem, a destructive belief that all events in their lives are beyond their control and less optimism about succeeding later in life (Worden, 1996;Schuurman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While there is a paucity of literature addressing the role of physical activity as a vehicle for helping bereaved children, there is a large body of research extolling the psychological health benefits of exercise. Studies have suggested that physical activity can enhance selfesteem (Fox, 2000), contribute to positive affect and mood (Biddle & Mutrie, 2001), help improve sleep (Arakawa et al, 2002;Morgan, 2003), reduce depression (Mutrie, 2000), help to manage the symptoms associated with schizophrenia (Carter-Morris & Faulkner, 2003), reduce stress (Read, Kahler, & Stephenson, 2001) and enhance body image (Ussher et al, 2000). Such evidence is particularly pertinent when we consider that bereaved children are more likely than other children to experience higher levels of depression, an increase in health problems and accidents, more anxiety and fear, lower self-esteem, a destructive belief that all events in their lives are beyond their control and less optimism about succeeding later in life (Worden, 1996;Schuurman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Seven involved clients seeking treatment through a type of residential program (e.g., supportive housing community, halfway house, recovery center; Boisvert, 2004;Boisvert, Martin, Grosek, & Clarie, 2008;Darko-Mensah, 2011;Martin, Bliven, & Boisvert, 2008;Peloquin, 2010;Ussher, McCusker, Morrow, & Donaghy, 2000;White, 2007), while the other three treatment settings involved an outpatient psychiatric facility (Cardinale, Malacari, Broggi, Savignano, & Fisher, 2014), an inpatient forensic psychiatric ward (Stevens, Redfearn, & Tse, 2003), and a prison (Tayer, 2004). Study size varied (n ¼ 1 to 75), along with length, frequency, and duration of intervention.…”
Section: Resultsmentioning
confidence: 99%
“…All studies focused on identifying life skill needs of participants to remain abstinent from their substance of choice, providing individuals with personal tools to prevent relapse (Boisvert, 2004;Boisvert et al, 2008;Cardinale et al, 2014;Darko-Mensah, 2011;Martin et al, 2008;Peloquin, 2010;Stevens et al, 2003;Tayer, 2004;Ussher et al, 2000;White, 2007). Of these, three reported additional treatment therapies (e.g., 12-step programs, individual counseling, and mental health services) being provided to clients at the stated facility, while simultaneously receiving occupational therapy treatment (Boisvert, 2004;Boisvert et al, 2008;Peloquin, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations